2013
DOI: 10.1063/1.4803926
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement in solar hydrogen generation efficiency using a GaN-based nanorod structure

Abstract: A significant enhancement in solar hydrogen generation has been achieved using a GaN-based nanorod array structure as a photoelectrode in comparison with a planar one fabricated from the same parent wafer. The nanorod array structure was formed by dry etching using a self-organised nickel nanomask. Under identical illumination conditions in hydrochloric acid solution, the photoelectrode with the nanorod array structure has demonstrated a photocurrent enhancement with a factor of 6 and an enhancement in the rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
59
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(60 citation statements)
references
References 14 publications
0
59
1
Order By: Relevance
“…Recently, GaN has been revealed as a material well suited for PEC water splitting and studied systematically [13][14][15][16][17]. On top, the progress in fabricating and characterizing InGaN nanostructures opens up new opportunities.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, GaN has been revealed as a material well suited for PEC water splitting and studied systematically [13][14][15][16][17]. On top, the progress in fabricating and characterizing InGaN nanostructures opens up new opportunities.…”
Section: Introductionmentioning
confidence: 99%
“…12 Although n-type GaN has a high absorption coefficient (10 5 cm -1 ) for supra bandgap light 13 and superior minority carrier diffusion length (200-300 nm), 14 recent studies have shown that the photoactivity of n-GaN can be significantly enhanced after surface roughening. [5][6][7] Surface roughening using wet etching techniques is desirable due to process simplicity and low costs. However, the superior chemical stability of the GaN (0001) plane, which is the predominant plane for GaN epitaxy, prevents etching by most chemicals.…”
Section: Introductionmentioning
confidence: 99%
“…17 Recently, GaN has been considered as a promising PEC electrode material, but also has a too large bandgap energy. [18][19][20][21][22] Therefore, considering the general requirements for efficient PEC water splitting, InGaN appears to be ideal with a bandgap energy tunable through the whole solar spectrum upon In composition, a large absorption coefficient, high carrier mobility, and good corrosion resistance. However, up to now there are only very few reports on the feasibility of solar water splitting using InGaN alloys.…”
mentioning
confidence: 99%